Questing Excellence in Academia A Tale of Two Universities - Sørensen, Knut H. (Routledge Studies in Science, Technology and Society, 2022)
Unlike almost most other studies of neoliberal universities and academic capitalism this book ethnographically explores and interprets those transformations and their contradictions empirically in the everyday practices of students, faculty members, and administrators at two public universities: NTNU in Norway and UCLA in California. Differently situated in global political economies, both are ambitious, prosperous campuses. The book refl exively examines their disturbing disputes about quality, competition, and innovation. It argues that some academic, bureaucratic, and corporate university governance practices are both unsustainable and undermining what some university students and faculty already do well: circulate interdisciplinary knowledge and its making globally across the diasporic domains of academia, society, industry, and government while addressing the world's immediate challenges: power, inequities, and sustainability. It shows the important, strategic work of domesticating, co- morphing, and meshworking at the faultlines of emerging knowledge. This book is for students, faculty, society members, and policy makers who want to engage more effectively with contemporary universities that increasingly serve as busy crossroads for sharing ideas and how to make them. It will be of interest to workers and scholars in the interdisciplinary fi elds of higher education studies, critical university studies, and critical public infrastructure studies, plus science, technology, and society studies.